Body Mass Index and Its Influence on Chronic Low Back Pain in the Spanish Population: A Secondary Analysis from the European Health Survey (2020) - María Orosia Lucha-López; César Hidalgo-García; Sofía Monti-Ballano; Sergio Márquez-Gonzalvo; Loreto Ferrández-Laliena; Julián Müller-Thyssen-Uriarte; Ana Carmen Lucha-López (Biomedicines, 2023)
Risk factors such as obesity and a sedentary lifestyle contribute to the development of chronic low back pain. Purpose: To describe how body mass index (BMI) influences the prevalence of chronic low back pain in the general Spanish population and assess this influence given other factors as sex, age, physical occupational demands, and recreational physical activity. Methods: An analytical cross-sectional design was performed based on secondary data from the European Health Survey in Spain (2020). Data on age, gender, physical occupational demands, physical activity, BMI, and presence of chronic low back pain were extracted. Results: A total of 19,716 (52.2% women) subjects with a median age of 53 years old were analyzed. Of these, 18.3% had chronic low back pain, 39% were overweight, and 16.1% were obese. The adjusted generalized linear model showed that being obese increased the odds of chronic low back pain by 1.719 times (p < 0.001). Being a woman increased the odds by 1.683 times (p < 0.001). Performing occupational tasks requiring high physical demands increased the odds by 1.403 times (p < 0.001). Performing physical activity in leisure time several times a week decreased the odds by 0.598 times (p < 0.001). For every additional year of age, the odds of chronic low back pain increased by 3.3% (p < 0.001). Conclusions: Obesity is related with the presence of chronic low back pain in the general Spanish population. This association persists, being the more relevant factor, after adjusting the association of BMI and chronic low back pain with other factors such as sex, age, physical occupational demands, and recreational physical activity.